Bilevel programs with extremal value function: global optimality - Abdelmalek Aboussoror; Hicham Babahadda; Abdelatif Mansouri (International Journal of Mathematics and Mathematical Sciences)
For a bilevel program with extremal value function, a necessary and sufficient condition for global optimality is given, which reduces the bilevel program to a max-min problem with linked constraints. Also, for the case where the extremal value function is polyhedral, this optimality condition gives the possibility of a resolution via a maximization problem of a polyhedral convex function over a convex set. Finally, this case is completed by an algorithm.